Komunikasi Pemasaran Dalam Meningkatkan Pembelian Impulsif Melalui Live Streaming Shopee Akun Holycatlabs.id - Aldo Renaldi; Rachmawati Windyaningrum (LPPM UNIBI, 2023)
PT. Holycatlabs Indonesia is a manufacturer and distributor of pet medicine and vitamins. The intense competition in the field of pet medicine and vitamin products has compelled PT. Holycatlabs Indonesia to establish various marketing channels, one of which is the Shopee marketplace. Shopee is an e-commerce platform or online marketplace founded by a Singaporean company named Sea Limited in 2015. The purpose of this study is to understand the phenomenon of marketing communication elements on impulsive buying behavior in Shopee's live streaming through the holycatlabs.id account. The researcher utilized a qualitative research method with a single instrumental case study approach. Data collection techniques employed in this study included interviews, observations, and literature studies. The research findings indicate that there are marketing communication elements utilized for impulsive buying in live streaming. These elements include vouchers, bundling, special live prices, and the personal branding of the host. However, there are several barriers for consumers to engage in impulsive buying in live streaming, such as technological limitations and internet access, trust and product credibility, lack of information and product descriptions, host's limited knowledge about the products, uncertainty about product quality, and the absence of suitable shipping options based on consumer preferences.